Promoting and selecting strategy-aligned projects through consensus in universities — An artifact - Fernando Pires Barbosa; Mauri Leodir Löbler (BAR: Brazilian Administration Review, 2020)
Project portfolio management has been studied through diverse aspects. Different approaches have been used to improve project portfolio selection, but not all of them have been actually used. This study presents an artifact to improve project portfolio selection process in universities. The artifact considers strategic alignment and focuses on achieving consensus, considering university characteristics about strategic planning and decision making environment. The artifact was developed through an incremental approach using quasi-experiments in simulated situations to check and improve the accuracy of the solutions being developed. Finally, the artifact was implemented in a real situation inside a university, involving 185 projects, 15 criteria, and 12 people from different faculties and knowledge areas. Results show that the artifact is suitable to the university environment. Beyond the artifact itself and some highlights involving its development process, the multicriteria constructivist approach, the balanced scorecard, and the scoring technique, another contribution is an adapted AHP tool created to integrate traditional AHP from Saaty (1980) and a study from Bose (2015) to reduce cognitive conflict in group decision making. Other studies, in more diverse contexts, still need to be done, but the proposal seems to be promised.